Climate Change: Causes, Impacts, Mitigation and Sustainable Adaptation Strategies (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Climate change has emerged as one of the most significant global environmental challenges of the twenty-first century. Anthropogenic activities such as fossil fuel combustion, industrialization, deforestation, urbanization, and unsustainable agricultural practices have intensified greenhouse gas emissions, leading to global warming and climate instability. The increasing concentration of greenhouse gases in the atmosphere has resulted in rising global temperatures, melting glaciers, sea-level rise, biodiversity loss, extreme weather events, and adverse impacts on human health, agriculture, water resources, and socio-economic systems. This research article provides a comprehensive overview of climate change, its scientific basis, causes, consequences, mitigation strategies, adaptation measures, and international policy responses. The study also discusses sustainable technological interventions, renewable energy systems, carbon sequestration, climate-smart agriculture, and the role of engineering and management approaches in combating climate change. Furthermore, the article highlights global agreements such as the Paris Agreement and the role of the Intergovernmental Panel on Climate Change (IPCC) in climate governance. The paper concludes that integrated global cooperation, technological innovation, environmental education, and sustainable development policies are essential to minimize climate risks and ensure a resilient future. Climate change is unequivocally caused by human activities, particularly greenhouse gas emissions, according to the latest IPCC synthesis findings.